People's knowledge, attitudes, practice, and healthcare education demand regarding OSA: a cross-sectional study among Chinese general populations - Pan, Zhongjing; Ma, Tianpei; Zeng, Qinghan; Xu, Ting; Ran, Qiong; Li, Tianming; Lu, Dan (Frontiers in Public Health, 2023)
Background: Population knowledge and attitudes toward obstructive sleep apnea syndrome (OSA) are critical to public health initiatives to overcome the disease. Health care education is an appropriate approach to expediting the process to build active medical practice models in the public. Objective: This study aimed to assess the level of knowledge, attitude, and practice (KAP) regarding OSA and health care education demand among the Chinese general population. Methods: A cross-sectional survey was performed online via Wenjuanxing in mainland China between February 8 and March 8, 2022, using a 34-item questionnaire designed and reviewed by multidisciplinary experts. Results: This study enrolled 1507 respondents, aged 18 to 68 years old, with a city to countryside ratio of approximately 2:1. Four-fifths of respondents reported that they had children (n=1237), and mothers accounted for 57.7%. If they or their children had symptoms of OSA, nearly nine in ten of respondents would undertake positive medical practices, especially parents. A total of 89.4% of the respondents reported a desire to receive health care education by the new multimedia approach, and most were concerned about the etiology of OSA. Conclusions: The current study indicated that even the higher educated and urban populations in mainland China had insufficient knowledge about, positive attitudes toward and practices regarding OSA, they showed an urgent demand for health care education. A special emphasis should be placed on appropriating population demand for health care education and promoting the benefits of active medical practice models in sleep medicine.